Recent Features and Industrial Applications of the Hybrid SPH-FE Method. Issue 1 (7th February 2021) - Groenenboom, Paul; Cartwright, Bruce; McGuckin, Damian
Abstract : This paper discusses selected features of the Smoothed Particle Hydrodynamics (SPH) method when used in combination with a Finite Element (FE) software tool. Special attention is paid to the implementation of wall boundary conditions in view of their relevance to the simulation of fluid-structure interaction (FSI). Several industrial applications of the hybrid SPH-FE method are reviewed in detail. These include the ditching of a fixed-wing aircraft, the ditching of a helicopter with an Emergency Flotation System, and the flooding of a ship due to a breach in the hull. The comparison of the results of the numerical study on fixed-wing aircraft against experimental data demonstrate the validity of the SPH method. It is concluded that the SPH-FE approach is well-suited for the simulation of violent flow phenomena and fluid-structure interaction.